Disruption of an adenylate‐forming reductase required for conidiation, increases virulence of the insect pathogenic fungus Metarhizium acridum by enhancing cuticle invasion. Issue 2 (3rd September 2019) - Guo, Haoyu; Wang, Hongjuan; Keyhani, Nemat O; Xia, Yuxian; Peng, Guoxiong
Abstract: BACKGROUND: Metarhizium acridum, is a specific acridid pathogen developed for use against the migratory locust ( Locusta migratoria manilensis ). Adenylate‐forming reductases (AFRs) include enzymes that are involved in natural product biosynthesis. Here, we genetically characterize the functions of a class IV AFR in M. acridum ( MaAfr IV ) on fungal development and virulence. RESULTS: Gene expression analyses indicated MaAfr IV was induced on locust wings early during the infection process. Surprisingly, loss of MaAfr IV increased virulence (25.20% decrease in the median lethal time) against the locust in topical bioassays but was no different than the wild type when the cuticle was bypassed by direct infection of conidia into the insect hemocoel. Virulence markers including protease ( Pr1 ) expression and appressorial turgor pressure were higher in the mutant than the parent strain. No difference was seen in the expression of host immune genes (Toll pathway) or in polyphenol oxidase (PPO) activity in locusts infected by the Δ MaAfr IV or wild type strains. However, the Δ MaAfr IV strain was unable to successfully sporulate on dead cadavers. CONCLUSION: Disruption of MaAfr IV increased fungal virulence by promoting insect cuticle invasion without altering host immune response or fungal immune evasion. Although loss of MaAfr IV conferred an apparent benefit to the fungus in terms of enhanced virulence, a significant trade‐off was seen in the inability of the fungus to sporulate on the cadaver. As conidiation on the cadaver is essential for subsequent propagation in the environment, loss of MaAfr IV can reduce the engineering strains survivability in the field and improve the safety. © 2019 Society of Chemical Industry Abstract : Knockout of the gene encoding AFR class IV in Metarhizium acridum increased the strain virulence and suppress the strain conidiation on the cadaver.